Stem cells of dental origin and their applications: A literature review - Moraes, Alan Ferreira de; Hartmann , Ivo (Seven Editora, 2023)
Stem cells are undifferentiated cells with the capacity for self-regeneration and formation of functional cells of tissues and organs. Current studies in biotechnology aim to understand and control the differentiation of these cells for scientific applications. Several types of stem cells are derived from dental tissues, including dental pontal stem cells (DPSCs), stem cells isolated from the pulp of exfoliated deciduous teeth (SHED), periodontal ligament stem cells (PDLSCs), apical papilla stem cells (SCAPs) and dental follicle cells (DFCs). These cells have potential for different applications in dentistry and tissue regeneration. Studies have investigated their properties and differentiation capacity for clinical and therapeutic use. The present review aims to evaluate what is known about these cells, as well as the possible clinical applications in regenerative therapies in current dentistry. DOI:https://doi.org/10.56238/globalhealthprespesc-066